Meson masses at finite temperature in a nonlocal Su(3) chiral quark model - Gomez Dumm, Daniel Alberto (2012)
We study the temperature behavior of light scalar and pseudoscalar meson masses within three-flavor nonlocal chiral quark model that includes the coupling of quarks to the Polyakov loop. Chiral restoration and deconfinement transitions are described.